From Currency Depreciation to Trade Reform : How to Take Egyptian Exports to New Levels? - Youssef, Hoda; Zaki, Chahir (World Bank, Washington, DC, 2019)
The Arab Republic of Egypt is yet to meet its exports potential, which has been historically hampered by several domestic market distortions and multiple barriers, resulting in weak export performance and modest regional and global integration. Although the liberalization of the exchange rate in November 2016 was a necessary step to correct the exchange rate misalignment and ease the ensuing shortages in foreign currency, it has not been sufficient to guarantee a notable improvement in export performance. This paper analyzes Egypt's exports along three dimensions that are key for export performance and future growth: (i) composition and relatedness of exported products; (ii) geographic and product concentration; and (iii) relatedness to globally traded products. The analysis suggests that Egypt continues to specialize in traditional areas of comparative advantage and limited value-added or is expanding toward products for which global demand is declining. The paper uses a gravity model to predict bilateral trade flows based on the economic size, geographic distance, and other relevant characteristics that should typically contribute to facilitated trade and identify specific sectors and markets for which Egypt seems to have an untapped potential. To understand this underperformance, the paper investigates the key impediments to meeting the export potential. It explores some of the important supply and demand side factors and assesses the role of trade policy measures (tariffs and non-tariffs barriers) in impeding export growth. The analysis reveals that despite significant liberalization efforts, Egypt remains among the group of developing countries that have the highest frequency index and coverage ratio of non-tariff measures. Policy recommendations include a call to improve external competitiveness by fostering and diversifying domestic production and complement these efforts by engaging in trade facilitation reforms to remove the non-tariffs barriers to trade, notably, the administrative, technical, and sanitary barriers to trade. These are all necessary for the country to capitalize on its competitive gains from the currency depreciation and to improve the degree of Egypt's integration into global markets.